PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII2 SMP NEGERI 1 DUMAI - Febrina Ramadhani; Rini Dian Anggraini; Elfis Suanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is students low in mathematical of grade at SMP Negeri 1 Dumai. The aims of research is to improve learning process and to increase student mathematics achievement with applying the learning model of Problem Based Learning. This research is classroom action research. The subject of this research is student of class VIII2 SMP Negeri 1 Dumai in academic years 2018/2019, which amounted to 32 students, consist of 15 boys and 17 girls. The research consist of two cycles, each cycle have four stages, which are planning, implementation, observation, and reflection. The instruments of data collection in this research is observation sheets that consisting of the identity of the observation sheet, filling instruction, indicators that refer to PBL steps, descriptors and observations and students mathematic tests. The observation sheets is analyzed in qualitative desciptive, while the students mathematic tests is analyzed in quantitative descriptive. The qualitative descriptive show an improvement of learning process prior to the action on the first and second cycle. Most of students are very confidence and active in learning process, such as while they are finishing mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. The results of this study indicate the number of students who reached Minimum Mastery Criteria of knowledge increase from basic score to quiz-I and quiz-II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (31,25%) to the first quiz (43,75%) to the second quiz (62,5%). For the skills of basic score (37,5%) to the first quiz (46,88%) to the second quiz (81,25%). From these data it can be concluded that the application of Problem Based Learning can improve learning process and increase mathematics achievement from the students at class VIII2 SMP Negeri 1 Dumai in academic years 2018/2019 for the subject relation and fungtion.Key Words: Students’ Mathematic Achievement, Problem Based Learning, Class Action Research